Perlindungan Hukum terhadap Aktivis Lingkungan Pada Penerapan Pasal Pencemaran Nama Baik - Muhammad Faiq Musyaffa; Wahyu Priyanka Nata Permana (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research examines legal protection for environmental activists in the application of defamation laws, particularly Article 27 paragraph (3) of the Electronic Information and Transactions Law (ITE Law). Environmental activists are often criminalized through defamation reports for voicing criticism or revealing facts about environmental damage by certain parties. The legal issues addressed are how legal protection is provided to activists charged with defamation and how judges interpret such cases under Supreme Court Regulation No. 1 of 2023. The study aims to understand how legal protection for environmental activies can be applied in court and how judges assess the protection of environmental activists. Using a normative juridical method, this research analyzes court decisions, case studies, and relevant legal sources. The findings show that many judges still misinterpret the application of legal protection, resulting in the continued criminalization of environmental activies. Therefore, a clearer legal interpretation is needed, especially concerning the existing guarantees of freedom of expression in Indonesia, to ensure consistent judicial protection and avoid conflicting rulings.